画中梦圆 ：陆行直《碧梧苍石图》及其题画词研究 = Painting the dysfunctional love : a study of Lu Xing Zhi’s Bi Wu Cang Shi Tu and the Poem Ci on the painting - 莫忠明 Bok, Zhong Ming (2016)
至治元年（ 1321）仲夏，书画家陆行直（1275－？）以友人张炎赠予的《清平乐》（‘候虫凄断’）为蓝本，创作《碧梧苍石图》。 二十一年后，行直感念张炎与画中女主角卿卿皆已尘沓，重题于卷首。在行直之后，有十四位元代文人以张炎之旧韵题词于画面，使《碧梧苍石图》成为元代文人酬酢唱和的代表作品。故此，本文拟从文图学的角度出发，先通过分析画面上的题画词，尝试还原行直与卿卿的关系，再透过中西方艺术理论，探究行直如何在绘画中进行文化编码，寄寓他们的爱情在精神上永不分离。最后，笔者亦探讨词与画两种截然迥异的艺术形式如何在画中进行融通，进而成就这幅图更高的艺术旨趣。笔者发现行直与卿卿的爱情实际上并不圆满，而行直透过《碧梧苍石图》的创作，在画中得到两人爱情上的圆满。On a summer day in the first year of Zhizhi (1321),Yuan literate Lu Xing Zhi painted a painting based on the Ci written for him by his friend, Zhang Yan. The painting, named Bi Wu Cang Shi, gained a lot of attention among researchers, as it was one of the most representative masterpiece in the Yuan Dynasty for having a total of 14 literates inscribing on the painting. This research will first analyse the Poem Ci on the painting, and through it, restitute the relationship between Lu Xing Zhi and his lover Qingqing. Through both Chinese and Western art theory, we would discuss how Lu Xing Zhi encodes the painting with cultural and social symbols and through it symbolized their inseparable love. Lastly, we will also discuss how Poem Ci and painting, the two seemingly different artistic category can be integrated together to present a higher level of aesthetic interest. Through this paper, we would discover the dysfunctional love between Xing Zhi and Qingqing and how Xing Zhi made use of his art piece to seek comfort and the love he and Qingqing failed to have.